Sustentabilidade e equilíbrio do crescimento: uma abordagem contábil-financeira - Oliveira, Antonieta Elisabete Magalhães (2010)
This paper combines two different fields of study – financial management and sustainability – that should be brought closer together, sharing concepts and practices, so that companies can contribute more effectively to the cause of sustainable development. The purpose of this work is to verify if balanced growth is in any way associated with a company’s sustainable performance. Assuming that unbalanced growth is a risk factor not only for a company but also for all its stakeholders, generating economic, social and environmental impact, it is to be expected that sustainable businesses would present a more balanced growth. The balanced growth indicator reflects the level of concern with how much pressure the company’s growth is putting on its resources and the way they are financed. The evaluation of a company’s sustainable performance should be broad, with emphasis on the concept of the Triple Bottom Line and on meeting the needs of all its stakeholders. In this study, what constitutes sustainable performance is defined in two ways: adherence to Bovespa’s corporate governance levels and participation in ISE-Bovespa, the corporate sustainability index created by the São Paulo Stock Exchange. The objectives are: to verify if the balanced growth indicator varies less in companies considered sustainable by the two criteria, assessed separately and combined, than in companies not deemed sustainable by the same criteria; and to verify if these same companies presented less variability of the balanced growth indicator during the second time frame of analysis than during the first. The two time frames are separated by the release of the first ISEBOVESPA portfolio in 2005. Data from listed companies pertaining to the period between December 1999 and December 2009 was used. The companies were divided in groups and the study focused on the variability of the balanced growth indicator, measured by standard deviation, within those groups, considering that all groups present means close to one. A group with low variability of the balanced growth indicator displays more concern with the measured use of its resources, reflecting an attitude in compliance with the notion that companies should contribute to the cause of sustainable development. The confirmation of ten of the twelve hypothesis raised by this analysis indicates that there is in fact a link between balanced growth and sustainable performance.